Study on Axial Compression Performance of Corroded Reinforced Concrete Columns Strengthened by Concrete Canvas and Carbon Fiber Reinforced Plastic under Secondary Corrosion - Fengge Li; Chen Chen; Zehui Xiang (Buildings, 2024)
To investigate the effects of concrete canvas (CC) and carbon fiber reinforced plastic (CFRP) reinforcement on the mechanical properties of corroded reinforced concrete columns (compressive strength, flexure strength, strength of extension, and so on), 42 columns in four groups were designed and axial compression experiments were carried out. For the corroded reinforced concrete columns reinforced with CC and CFRP, the effects of initial corrosion rate (5%, 10%), secondary corrosion time (15 d, 30 d), number of CC layers (0, 1), and number of CFRP layers (1, 2, 3) on the failure morphology, load carrying capacity, and ductility of concrete columns were analyzed. The test results show that the properties of the single layer CC confined specimens are improved to a certain extent, and the ductility properties are enhanced. The properties of the CC–CFRP composite constrained specimens are greatly improved, the plastic deformation ability is enhanced, and the typical ductile damage characteristics are shown. The corrosion inhibition of CC for specimens with a theoretical corrosion rate lower than 20% showed an increasing trend, and the corrosion inhibition rate ranged from 23.0% to 31.2%. CC and CFRP restrain the concrete jointly, hindering the expansion inside the concrete, and the peak strain of the joint restraint specimen itself changes greatly, while the overall peak strain of the corrosion specimen is very small under the action of the joint steel bar. Finally, according to the existing peak stress–strain model and the experimental data in this paper, a peak stress–strain model suitable for corroded reinforced concrete columns is established. The established calculation model has a high accuracy, which provides a certain theoretical basis for subsequent research.